Religion and bank loan terms - He, Wen; Hu, Maggie (Rong) (Journal of Banking & Finance, 2016)
We examine whether religion affects the terms of bank loans. We hypothesize that lenders value the traits of religious adherents, such as risk aversion, ethical behavior and honesty, and thus offer favorable loan terms to religious borrowers. Consistent with this hypothesis, we find that corporate borrowers located in counties with a high level of religiosity are charged lower interest rates, have larger loan amounts and fewer loan covenants. These results suggest that the corporate culture of borrowers influences the availability and cost of bank loans.